Disposition of 1,4,6,8-Tetramethyl-furoquinolinone in Normal and Ascitic Tumor Bearing Mice - Bevilacqua, Rita; Baccichetti, Francarosa; Gaion, Rosa Maria; Guiotto, Adriano (Arzneimittelforschung, 2006)
1,4,6,8-Tetramethyl-2H-furo[2,3-h]quinolin-2-one (FQ) belongs to a series of furocoumarin isosters, designed to obtain new drugs for photochemotherapy. The objective of this study was to characterize the disposition of orally administered 3H-FQ in normal and ascitic tumor bearing mice and to evaluate the influence of UVA irradiation in control mice. This compound was rapidly absorbed and its decay in serum was biphasic. Binding to serum proteins, which was maximum at 30 min (74 %), time-dependently declined. FQ was distributed to all the studied tissues, primarily to the liver and kidneys. The administered radioactivity was excreted mostly in the urine (43 %) and was associated with polar metabolites. The unchanged compound was not present to any detectable extent in the urine. Elimination in the faeces, that may include FQ not absorbed, was low (14 % of administered radioactivity), emphasizing the quantitatively efficient gastrointestinal absorption of the drug. UVA irradiation of FQ-treated mice for 2 h caused a significant increase in radioactivity measured in serum as well as in the liver. In mice bearing Ehrlich ascitic tumor, serum and tissue concentrations were lower than in control animals, possibly due to the larger volume of body fluids (10 ± 4 ml of ascitic fluid) available for drug distribution.
Keywords: Furocoumarins; Furoquinolinones, pharmacokinetics, PUVA therapy, tumor bearing mice; Photochemotherapeutics; Psoralens